2014
DOI: 10.1152/ajpheart.00868.2013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NADPH oxidase prevents acute lung injury in obese rats following severe trauma

Abstract: Lung capillary filtration coefficient (Kf) and impacts of oxidative stress have not been determined in the setting of severe trauma, especially in obese patients who exhibit increased lung injury. We hypothesized that severe trauma leads to a greater increase in lung Kf in obesity due to exacerbated production of and/or vulnerability to oxidative stress. Severe trauma was induced in lean and obese Zucker rats by muscle injury, fibula fracture, and bone component injection to both hindlimbs, with or without 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…We found increased ALI in OZ rats 1 day after trauma, as indicated by neutrophil retention, elevated lung MPO activity, increased capillary permeability (48), and lung edema. Inhibition of the increased early hyperglycemia by ICI treatment prevented the development of ALI in OZ rats.…”
Section: Significance and Clinical Relevancementioning
confidence: 62%
See 3 more Smart Citations
“…We found increased ALI in OZ rats 1 day after trauma, as indicated by neutrophil retention, elevated lung MPO activity, increased capillary permeability (48), and lung edema. Inhibition of the increased early hyperglycemia by ICI treatment prevented the development of ALI in OZ rats.…”
Section: Significance and Clinical Relevancementioning
confidence: 62%
“…Hyperglycemia has been shown to increase ROS and affect neutrophil responses, including neutrophil retention (27) and exacerbated free radical release (28), which are important processes in innate immune responses (22,49) and ALI. Indeed, our previous study (48) showed that early antioxidant treatment after severe trauma targeting the enzyme responsible for the neutrophil respiratory burst decreases systemic inflammation and prevents the development of ALI in OZ rats. The underlying mechanisms whereby early posttrauma hyperglycemia increases later adverse outcomes are unclear and beyond the scope of the present study.…”
Section: Significance and Clinical Relevancementioning
confidence: 98%
See 2 more Smart Citations
“…We have shown that the day after orthopedic trauma, obese rats exhibit increased incidences of acute lung and acute kidney injury, the two most-frequent organ injuries observed in trauma patients. This is evidenced by the presence of greater lung inflammation and pulmonary edema, decreased glomerular filtration rate and renal plasma flow, and increased urine excretion of renal damage markers in obese Zucker rats as compared to their lean counterparts (58, 96). This is in agreement with the clinical literature, which has consistently demonstrated an increased risk of multiple organ (especial lung and kidney) dysfunction, injury, and failure in obese blunt trauma patients (11, 20).…”
Section: Obesity and Animal Models Of Critical Illnessmentioning
confidence: 99%